A Host-Produced Quorum-Sensing Autoinducer Controls a Phage Lysis-Lysogeny Decision - Silpe, Justin E. (Cell, 2018)
Vibrio cholerae uses a quorum-sensing (QS) system composed of the autoinducer 3,5-dimethylpyrazin-2-ol (DPO) and receptor VqmA (VqmA(Vc)), which, together, repress genes for virulence and biofilm formation. vqmA genes exist in vibrios and in one vibriophage, VP882. Phage-encoded VqmA (VqmA(Phage)) binds to host-produced DPO, launching the phage lysis program via an antirepressor that inactivates the phage repressor by sequestration. The antirepressor interferes with repressors from related phages. Like phage VP882, these phages encode DNA-binding proteins and partner antirepressors, suggesting they too integrate host-derived information into their lysis-lysogeny decisions. VqmA(Phage) activates the host VqmA(Vc) regulon, whereas VqmA(Vc) cannot induce phage-mediated lysis, suggesting an asymmetry whereby the phage influences host QS while enacting its own lytic-lysogeny program without interference. We reprogram phages to activate lysis in response to user-defined cues. Our work shows that a phage, causing bacterial infections, and V. cholerae, causing human infections, rely on the same signal molecule for pathogenesis.